2016
DOI: 10.1002/ecy.1537
|View full text |Cite
|
Sign up to set email alerts
|

Foliar bacteria and soil fertility mediate seedling performance: a new and cryptic dimension of niche differentiation

Abstract: Abstract. The phyllosphere (comprising the leaf surface and interior) is one of the world's largest microbial habitats and is host to an abundant and diverse array of bacteria. Nonetheless, the degree to which bacterial communities are benign, harmful, or beneficial to plants in situ is unknown. We tested the hypothesis that the net effect of reducing bacterial abundance and diversity would vary substantially among host species (from harmful to beneficial) and this would be strongly mediated by soil resource a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 71 publications
5
42
4
Order By: Relevance
“…Fertilization often increases tissue nutrient concentrations (Fig. Potassium addition also reduced net adverse effects of foliar bacteria in our experiment (Griffin et al 2016). Two fertilization experiments conducted in LSRTF considered herbivory.…”
Section: Experimental Evidence For Nutrient Limitationmentioning
confidence: 64%
“…Fertilization often increases tissue nutrient concentrations (Fig. Potassium addition also reduced net adverse effects of foliar bacteria in our experiment (Griffin et al 2016). Two fertilization experiments conducted in LSRTF considered herbivory.…”
Section: Experimental Evidence For Nutrient Limitationmentioning
confidence: 64%
“…We previously demonstrated that Agry‐gent and Agri‐mycin significantly decreased mean abundance of epiphytic and endophytic bacteria by over 50% on our focal species and also decreased microbial morphotype richness by over 20% (Griffin et al ., ). Each of these antibiotic treatments were equally effective and remained so over time; also, their impact was very similar among nutrient treatments and plant species (Griffin et al ., ). Thus, our antibiotics worked in the sense that they reduced foliar bacterial loads, although our results are likely conservative because we only reduced bacterial abundance and richness by c .…”
Section: Resultsmentioning
confidence: 97%
“…Overall, our findings support recent studies that challenge the conventional wisdom that light is only a limiting resource for tropical seedlings and moreover demonstrate that soil nutrient availability and foliar bacteria are major drivers of plant performance (e.g. Pasquini & Santiago, ; Santiago et al ., ; Pasquini et al ., ; Griffin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations